Boron for tissue regeneration-it's loading into chitosan/collagen hydrogels and testing on chorioallantoic membrane to study the effect on angiogenesis. Issue 8 (23rd May 2020) - Ahtzaz, Samreen; Sher Waris, Tayyaba; Shahzadi, Lubna; Anwar Chaudhry, Aqif; Ur Rehman, Ihtesham; Yar, Muhammad
Abstract: In the current study, boric acid loaded chitosan (CS) and collagen-based hydrogels were prepared. Hydrogels with four different boric acid concentrations were prepared; control hydrogel (without boric acid), and a hydrogel having boric acid 50 mg (B50), 250 mg boric acid (B250) and 500 mg boric acid (B500). Internal morphology of hydrogel was determined by performing scanning electron microscopy (SEM). Internal linkages of functional groups were confirmed by Fourier transform infrared spectroscopy (FT-IR). The pro-angiogenic potential of these materials was explored in chorioallantoic membrane (CAM) assay and 50 mg boric acid (B50) based hydrogel showed comparatively higher angiogenesis. GRAPHICAL ABSTRACT: